2017
DOI: 10.1373/clinchem.2016.269605
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Signatures in Circulating Tumor Cells Correlate with Response to Therapy in Metastatic Breast Cancer

Abstract: could be a key marker in distinguishing R from NR, and was powerful in identifying CTCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…These data showed that the isolation of CTCs occurred in a specific manner and that the epithelial population isolated with the CellSearch ® approach was also harvested with this strategy. Furthermore, Bredemeier and colleagues described KRT19 as a powerful marker to identify CTCs in metastatic breast cancer (MBC) [31]. We also found that KRT19 was higher in luminal patients versus TNBC.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These data showed that the isolation of CTCs occurred in a specific manner and that the epithelial population isolated with the CellSearch ® approach was also harvested with this strategy. Furthermore, Bredemeier and colleagues described KRT19 as a powerful marker to identify CTCs in metastatic breast cancer (MBC) [31]. We also found that KRT19 was higher in luminal patients versus TNBC.…”
Section: Discussionsupporting
confidence: 62%
“…In this sense, some studies have explored CTCs in BC by using molecular methods [21][22][23][24][25][26][27][28]. However, only a few have evaluated the characteristics of CTCs after therapy [19,26,[29][30][31], and, to our knowledge, only one has used a negative enrichment approach comparable with ours [32].…”
Section: Discussionmentioning
confidence: 99%
“…Reijm et al, developed an 8-gene expression profile in CTCs which discriminates good and poor outcome to first-line aromatase inhibitors in MBC patients [37]. Bredemeier et al, also reported gene expression signatures in CTCs that can be used to monitor response to therapy in MBC [38]. It was also demonstrated that changed gene expression during first-line systemic therapy for MBC could be a possible explanation for treatment resistance [39].…”
Section: Changes In Expression; Reversible Re-programingmentioning
confidence: 99%
“…uPA is coded for by the Plasminogen Activator Urokinase ( PLAU ) gene and activates plasminogen via conversion to plasmin (Mahmood et al, ). Association between shear stress stimulus and the uPA system modulation has been shown for proximal tubular cells (Essig & Friedlander, ), endothelial cells (Diamond, Eskin, & McIntire, ; Dolan, Sim, Meng, & Kolega, ; Sokabe et al, ), and smooth muscle cells (Papadaki et al, ); although PLAU upregulation has been linked to metastatic cancers as a possible biomarker (Bredemeier et al, ; Sepiashvili et al, ; Tang & Han, ), it has yet to be directly tied to mechano‐stimulus in cancer.…”
Section: Introductionmentioning
confidence: 99%